2021
DOI: 10.1016/j.csbj.2021.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric pockets and dynamic residue network hubs of falcipain 2 in mutations including those linked to artemisinin resistance

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 98 publications
0
39
0
Order By: Relevance
“…Factoring in the size of the protein, we calculated and analyzed the hubs for each metric for 2, 3, 4, and 5% and identified that the global top 4% residue data were the most informative. As previously established, 38 4% hub data for each metric are presented as a heat map. Analysis of each of the heat maps is detailed in the following subsections.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Factoring in the size of the protein, we calculated and analyzed the hubs for each metric for 2, 3, 4, and 5% and identified that the global top 4% residue data were the most informative. As previously established, 38 4% hub data for each metric are presented as a heat map. Analysis of each of the heat maps is detailed in the following subsections.…”
Section: Resultsmentioning
confidence: 99%
“…It is used to identify key allosteric residues 57 as well as mutation and ligand-induced residue network changes in a variety of proteins. 38 , 41 , 58 , 59 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural modeling combined with network theory has been widely exploited in studying protein topology, dynamics and allostery [ 26 28 ]. Dynamic network modeling of conformational ensembles has been proven as an efficient approach to describe structural and dynamic changes associated with mutational effects in complex protein systems [ 29 32 ]. Central to these approaches is characterization of conformational protein dynamics and mutation-induced changes in the protein equilibrium ensembles which is fundamental to understanding the physical basis of the effects of missense variants [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%